Evidence based recommendations to improve the children oral health in Saudi Arabia - Falah R. Alshammari; Arwa A. Alsayed; Mohammad Albakry; Marwan Aljohani; Hassan Kabbi; Hamdan Alamri (Saudi Dental Journal)
Aim: Identify the existing evidence base with regards to interventions that address high levels of dental caries. A discussion of the applicability of the evidence to possible replication in Saudi Arabia is presented, alongside recommendations to help reduce dental caries rates in children in Saudi Arabia. Methods: A comprehensive systematic review following PRISMA methods was conducted using three databases: MEDLINE via OVID; EMBASE via OVID and Cochrane Library. Studies were included according to inclusion criteria. AMSTAR2 was used to assess the quality of the included studies, while GRADE was used to assess the quality of evidence. Results: Ten studies were included in this review. The quality of these were ‘high’ (in two review), moderate (in two studies), low (in one study) and to ‘critically low’ (5 reviews). The quality of the evidence presented by the reviews ranged from ‘moderate’ to ‘very low’. The interventions methods included MI, one-to-one nutrition advice, educational interventions and dental screening. The applicability of the findings in relation to dental care in Saudi Arabia is discussed and summarized in a narrative. Conclusion: No strong evidence that supported interventions to improve the child oral health in Saudi Arabia was found. None of the included reviews included studies conducted in Saudi Arabia or evaluated interventions among the local community. As for different culture values, norms, beliefs and attitude to those demographics explored in the reviews, it is unclear if interventions with improve oral health among Saudi children. Further research is needed to explore the efficacy of these interventions in a Saudi context.